2020
DOI: 10.1140/epjc/s10052-019-7596-4
|View full text |Cite
|
Sign up to set email alerts
|

Study on wormhole geometry with $$\rho (R, R^{'})$$ matter in modified gravity

Abstract: In this work, static traversable wormholes are investigated in R 2 gravity with logarithmic trace term T , where R denotes the Ricci scalar, and T = −ρ + p r + 2 p t > 0, the trace of the energy momentum tensor. The connection between energy density of the matter component and the Ricci scalar is taken into account. Exact wormhole solutions are determined for three different novel forms of energy density: ρ = α

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…Can observations be used to test if specific black holes are wormholes? We explore a proposal, first discussed by [6], to look for the effect of a perturbing object, orbiting on the other side of the wormhole, on the orbit of a star on our side (for other methods see e.g., [7][8][9][10][11][12][13][14][15][16][17]). Can we reasonably expect perturbers to orbit on the other side of a wormhole?…”
mentioning
confidence: 99%
“…Can observations be used to test if specific black holes are wormholes? We explore a proposal, first discussed by [6], to look for the effect of a perturbing object, orbiting on the other side of the wormhole, on the orbit of a star on our side (for other methods see e.g., [7][8][9][10][11][12][13][14][15][16][17]). Can we reasonably expect perturbers to orbit on the other side of a wormhole?…”
mentioning
confidence: 99%
“…where N f b is given by Eq. (39). The radial NEC is same for closed universe as well as open universe.…”
Section: Eu In Closed/open Backgroundmentioning
confidence: 99%
“…The prediction that the universe may be composed of unknown cosmic fluids in addition to normal matter led to scrutiny for cosmological models for a realistic scenario with dark energy (DE), phantom, Chaplygin gas [29][30][31][32] etc.. The phantom field [33][34][35], Chaplygin gas [36], DE [37][38][39] are employed to obtain wormholes. Böhmer et al [40] obtained a class of wormhole solutions systematically with exotic matter restricted to the throat neighbourhood and with a cutoff 0123456789().…”
Section: Introductionmentioning
confidence: 99%
“…They showed that for negative second-order and positive third-order Lovelock coefficients, there are thin-shell wormholes respecting the weak energy condition. For further modified gravity wormholes one can check [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%